2014
DOI: 10.1007/s00262-014-1581-4
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 expression in T regulatory cells and other cell lineages

Abstract: Forkhead box P3 (Foxp3) is an important transcription factor that belongs to the forkhead/winged-helix family of transcriptional regulators. Foxp3 has been extensively studied over the past 13 years as a master regulator of transcription in a specific T-cell type, CD4(+) regulatory T cells (Treg), both in humans and in mice. Compelling data characterize Foxp3 as critically important and necessary for the development and the differentiation of Treg. It has been considered initially as the only specific marker f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 82 publications
1
62
0
Order By: Relevance
“…Using the Human Protein Atlas [15, 16], we first quantified expression of Foxp3, a bona fide marker for Tregs [18, 19], in primary tumors of several solid cancers using immunohistochemistry. We found that Foxp3 + Tregs were detected in human pancreatic cancer at a frequency comparable to colorectal and lung cancers and higher than that seen in melanoma and prostate cancer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using the Human Protein Atlas [15, 16], we first quantified expression of Foxp3, a bona fide marker for Tregs [18, 19], in primary tumors of several solid cancers using immunohistochemistry. We found that Foxp3 + Tregs were detected in human pancreatic cancer at a frequency comparable to colorectal and lung cancers and higher than that seen in melanoma and prostate cancer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have proposed that FOXP3 is not only expressed by Tregs, but can be expressed by other types of lymphoid or myeloid cells, and by some non-haematopoietic cells such as epithelial cells [40]. To further specify the phenotype of FOXP3+ cells we performed dual immunofluorescence staining on synovial tissue sections with anti-CD4 and anti-FOXP3 antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…The ) cells (4). CD patients, however, seem to be more responsive to lactate and show an increase in the total pool of FoxP3 1 cells compared to HC as a possible compensatory mechanism to maintain a high level of functional FoxP3 1 FL isoform (5). During the active state of the disease the small intestine of CD patients is characterized by a drop in lactate levels, an increased intestinal permeability due to the interaction between gliadin and epithelial cells (6) and high production of butyrate from the microbial flora (7).…”
Section: Regulation Of Foxp3 Isoforms In Coeliac Diseasementioning
confidence: 99%
“…T reg cells can mediate suppression of responder cells through different mechanisms, including the production of immunosuppressive cytokines, the consumption of IL-2 and the down-regulation of costimulatory molecules on antigen-presenting cells (APC) [3]. The nuclear transcription factor forkhead box protein 3 (FoxP3) has been described to be fundamental in regulating the differentiation and function of T reg cells [4,5]. Indeed, mutations located on the FOXP3 gene have been associated with the onset of several autoimmune diseases, such as immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome (IPEX), type 1 diabetes, Grave's disease and systemic lupus erythematosus (SLE) [6][7][8][9][10].…”
Section: Regulatory T Cells (T Reg ) Represent a Subset Of Cd4mentioning
confidence: 99%